Use of the Angularis Oris Axial Pattern Buccal Flap for the Correction of Facial Defects in Six Dogs - Frasson, Maria Tereza (2020)
Background: Reconstructive surgery is an important area of veterinary surgery because it allows the reconstruction of large cutaneous defects in areas where a primary approach is not possible. Axial patterns flaps are composed by one direct cutaneous artery and vein, leading to a better blood supply with a good survival outcome. The angularis oris axial pattern buccal flap was introduced for correction of facial defects, but its versatility is not really explored in the existing literature. This article reports the use and complications of the angularis oris axial pattern buccal flap in six dogs, to treat defects in mandibular, temporal or labial regions. Cases: Five mixed breed dogs and one Labrador, with age between 4 and 9-year-old were submitted for surgery and the angularis oris axial pattern buccal flap was used to close the different defects. Causes of defect included a lesion caused by myiasis in three of the dogs, and tumoral removal in the other three, where two were mast cell tumors and one a keratinizing basal cell carcinoma. The regions affected included rostral mandible with oral mucosa, intermandibular region, temporal region and upper lip. Before flap confection the tissue was cleaned, resected and prepared properly, according to each cause of lesion. The flap was made with two parallel incisions, which center was usually the labial commissure, with the dorsal limits at the ventral aspect of the zygomatic arch, and the ventral incision on the ventral aspect of the mandibular ramus. Caudal extension was based on the length needed for surgical closure, but stained between the vertical auditory canal or up to atlas wing. Suture size and pattern depend the region and patient size. Patients were observed closely for any complication in the surgical site. From the six dogs presented here, five got some complications in the surgical site, including: lymphedema (2), suture dehiscence (4) and hematoma (1); however, regardless the complication, all patients had successful wound healing in 15 to 21 days after surgery. Also, in two of the four suture dehiscence episodes, the cause of dehiscence was secondary to trauma and not the surgery. Discussion: The reconstruction of facial defects is noteworthy due the limited availability of flaps that can reach the region without excessive tension or healing complications. The angularis oris axial buccal flap pattern is the nearest flap to close defect in the intermandibular, temporal or labial regions. In the cases reported, it is possible to observe that the most frequent complication was suture dehiscence, but it occurred mostly in a small proportion of the flap, allowing healing in the expected time. The surgical planning is an important factor for reconstructive surgeries, so that there is enough tissue for the closure of the recipient and donor site, without tension over the flap or interference with tissue function and aesthetics. Despite the suture dehiscence in some of the cases, all patients showed adequate final recovery, since they returned to normal function with satisfactory cosmetic appearance. The angularis oris axial pattern buccal flap was applied in the correction of defects easily and all patients returned to normal function with satisfactory cosmetic appearance.